Guidance differs between teaching modes: practical challenges in integrating hands-on investigations with direct instruction. (3rd July 2022) - Zhang, Lin
ABSTRACT: Integrating scientific investigations into science instruction has been a global phenomenon. Particularly in the US, this emphasis has been suggested by the nation-wide science educational standards over decades. However, the details on how the integration could be carried out remain under discussed. The present study focuses on the integration of hands-on investigations with direct instruction and examines a high-school physics unit that incorporated both instructional modes. This study found that what was offered in the guidance and how it was offered differed substantially when teaching shifted between the two modes, which led to difficulties in the integration in teaching practice. This study provides suggestions and calls for studies to look into this issue.